Gender, hidden profiles, and the individual preference effect. Issue 8 (11th December 2021) - Nicholson, Dawn H.; Hopthrow, Tim; Randsley de Moura, Georgina
Abstract: In this paper, we meta‐analyzed nine of our own studies to examine gender effects in decision‐making when information is asymmetrically distributed among group members in a hidden profile (HP). In particular, we examined the influence of individual preferences on decision‐making outcomes and how, or whether, they differed by gender. The meta‐analysis of our studies, which focused on individual decision‐making, suggested that the individual preference effect (IPE), a form of confirmation bias, may manifest differently by gender: Female participants in the HP condition demonstrated greater improvement in decision quality when moving from viewing partial to full information than their male counterparts. No gender differences in decision quality were found when information was presented in a structured one‐page Manifest Profile (MP), with all information made immediately available to all participants. This gender differential in the IPE is not contemplated by previous IPE or HP research, so this finding is of significant interest. We discuss our results in the context of previous mixed findings regarding the effect of gender diversity in improving group decision‐making and potential workplace changes required to recognize this gender difference.